Neurogenic Stunned Myocardium in Two Children with Neurological Injury - Díaz Ruiz, Laura; Durán Lorenzo, Iria; Ordoñez Sáez, Olga (Journal of Pediatric Intensive Care, 2019)
Neurogenic stunned myocardium is described as sudden and reversible cardiac dysfunction induced by an acute neurological event. This phenomenon has not been thoroughly investigated in infants, and is probably underdiagnosed. Here, we report the cases of two infants with neurogenic stunned myocardium in whom the clinical suspicion was relevant, with a brief discussion of this condition.
Keywords: neurogenic stunned myocardium; cardiac dysfunction; physical child abuse